2023
DOI: 10.3390/mi14081494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Migration on the Stress Field in Microfluidic Flows of Blood Analog Fluids at High Reynolds Numbers

Finn Knüppel,
Ang Sun,
Frank-Hendrik Wurm
et al.

Abstract: In the present paper, we investigate how the reductions in shear stresses and pressure losses in microfluidic gaps are directly linked to the local characteristics of cell-free layers (CFLs) at channel Reynolds numbers relevant to ventricular assist device (VAD) applications. For this, detailed studies of local particle distributions of a particulate blood analog fluid are combined with wall shear stress and pressure loss measurements in two complementary set-ups with identical flow geometry, bulk Reynolds num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In this Reynolds number definition, c represents bulk velocity, and denote density and viscosity (measured in a rheometer), and L is the characteristic length. Similarly to Fåhræus and Lindqvist, the study of Knüppel et al [ 15 ] revealed a significant reduction in stresses and pressure losses across the gap at high . Based on this experimental basic research, it was anticipated that a particle migration will also occur within real VAD gap flows, significantly influencing the flow dynamics in the gap.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…In this Reynolds number definition, c represents bulk velocity, and denote density and viscosity (measured in a rheometer), and L is the characteristic length. Similarly to Fåhræus and Lindqvist, the study of Knüppel et al [ 15 ] revealed a significant reduction in stresses and pressure losses across the gap at high . Based on this experimental basic research, it was anticipated that a particle migration will also occur within real VAD gap flows, significantly influencing the flow dynamics in the gap.…”
Section: Introductionmentioning
confidence: 79%
“…The foundation of the model lies in the experimental analysis of particle distribution within a particle-laden gap flow operating at high Reynolds numbers. For a comprehensive understanding of the experimental setup, readers are directed to our earlier publication in Knüppel et al [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations